RJASAMA FRED HOLLOWS FOUNDATIONS (FHF) DENGAN TILGANGA INSTITUE OF OPHTHALMOLOGY (TIO) DALAM MENGATASI MASALAH KEBUTAAN DI NEPAL TAHUN 2011 – 2014 - Silalah, Benny Patria; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research will explain about cooperation between two inter non-governmental organinization named Fred Hollows Foundations (FHF) from Australia and Tilganga Institute of Ophthalmology(TIO) from Nepal. As one of the poorest country in South Asian, desease that causing blindness. Geographical conditions which are in southern Nepal Himalaya make this country has a low level of eye health. This is due to the difficulty of patients to gain access to public services which are mostly located in the capital of Nepal, Kathmandu. FHF works together with TIO to carry out eye health care program such as OMEC (Outreach Microsurgical Eye Camp), Geta Eye Hospital, Training and Infrastructure Development, Advocacy.Sources were obtained through literature revivew from books, journals, reports, and internet to explain FHF and TIO programs. The writer using pluralism as a perspective and cooperation theory as a theory.The survey of blindness in Nepal has been done twice in 1981 and 2010. This research describe cooperation between FHF dan TIO in 2011-2014 to ending blindness after the last survey and see the results of cooperation on the level of blindness in Nepal.Keywords: Fred Hollows Foundations, Tilganga Institute Of Ophthalmology, cooperation, ending blindness